FIRST SKELETAL REMAINS OF HELVETICOSAURUS FROM THE MIDDLE TRIASSIC ITALIAN OUTCROPS OF THE SOUTHERN ALPS, WITH REMARKS ON AN ISOLATED TOOTH (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
The enigmatic marine reptile Helveticosaurus zollingeri, from the Middle Triassic Besano Formation of Monte San Giorgio, is known from three specimens found in Swiss territory. This paper describes the first skeletal remains of this taxon recovered from the corresponding Italian outcrops of Besano (Varese). An isolated tooth assigned to the same taxon and coming from the San Salvatore Dolomite, Rasa di Varese (Varese), is also redescribed herein. The skeletal remains have been CT scanned to inspect the preserved morphology of the bones hidden below the surface; CT data also allowed the identification of an associated ammonoid which has been crucial to determine the stratigraphic position of the studied material. The redescription of the tooth has been helped by a digital model of the specimen obtained through photogrammetry. With the additional new data obtained from the two specimens, the first skeletal reconstruction of Helveticosaurus is provided. This is followed by a phylogenetic test of the taxon, assessing its position among marine Triassic diapsids. Finally, in the light of recent studies we discuss the swimming mode and the possible ecological niche occupied by the animal: we suggest a distinction between the function of forelimbs and hindlimbs, and a distinction between different swimming styles likely performed by Helveticosaurus, depending on the speed of movements.
Keywords: Helveticosaurus; Diapsida; Besano Formation; Middle Triassic; Monte San Giorgio; Italy.